2016
DOI: 10.1007/s13204-016-0530-2
|View full text |Cite
|
Sign up to set email alerts
|

A study on corrosion resistant graphene films on low alloy steel

Abstract: Graphene nanosheets were produced after synthesizing graphene oxide via Hummer's method and a modified Hummer's method. The obtained graphene after reduction was dispersed in 1-propanol to get a coating solution. Mild steel coupons were coated with the graphene solution via dip coating method. Corrosion studies were carried out at different environments like water (pH 6.0), HCl (0.1 N), NaCl (3.5 wt%) and NaOH (1 M). Tafel analysis showed a reduction in the corrosion rate up to 99 % after three layer depositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…In our earlier study [2], the graphene nanosheets coated copper exhibited a very less negative E corr value (−211.0 mV) in comparison to bare copper (−691.4 mV), and I corr value of 4.0 µA/cm 2 in comparison to bare copper (38.25 µA/cm 2 ) in 3.5% NaCl. In another study, Sai et al [53] reported 91% corrosion inhibition efficiency by dip-coated rGO on mild steel when tested in 3.5% NaCl. However, such improvement in corrosion inhibition efficiency was achieved on samples coated for three times by dip coating, because a single dip-coating produced incomplete coverage of the surface.…”
Section: Discussionmentioning
confidence: 96%
“…In our earlier study [2], the graphene nanosheets coated copper exhibited a very less negative E corr value (−211.0 mV) in comparison to bare copper (−691.4 mV), and I corr value of 4.0 µA/cm 2 in comparison to bare copper (38.25 µA/cm 2 ) in 3.5% NaCl. In another study, Sai et al [53] reported 91% corrosion inhibition efficiency by dip-coated rGO on mild steel when tested in 3.5% NaCl. However, such improvement in corrosion inhibition efficiency was achieved on samples coated for three times by dip coating, because a single dip-coating produced incomplete coverage of the surface.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, most corrosion research surrounding 2D materials has been carried out in simulated seawater containing 3.5 wt% of NaCl, which mimics a marine environment. For example, a layered graphene coating on mild steel has been shown to reduce the corrosion rate due to its barrier effect in seawater ( Figure 2) [57].…”
Section: Marine Environmentmentioning
confidence: 99%
“…In fact, most corrosion research surrounding 2D materials has been carried out in simulated seawater containing 3.5 wt% of NaCl, which mimics a marine environment. For example, a layered graphene coating on mild steel has been shown to reduce the corrosion rate due to its barrier effect in seawater ( Figure 2) [57]. Optical microscopic image of (a) bare mild steel and (b) graphene-coated mild steel after corrosion test in 3.5 wt% NaCl for 1 h. Bare mild steel corrodes severely compared to graphene-coated mild steel in simulated seawater.…”
Section: Marine Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Mild steel coupons were coated from the synthesized graphene solution. Three layers of graphene films were able to reduce the corrosion rate by 99 % [11].…”
Section: Prospect Of Pipelines Defence From Corrosion With the Help Omentioning
confidence: 99%